The Influence of Online Customer Reviews and Trust on Purchasing Decisions on the Shopee Marketplace in the Community Unit 08, Pasirkaliki Urban Village, North Cimahi District, Cimahi City - MUHIBAN, Ayi; ANGGRAENI, Dhea (Journal of Entrepreneurial and Business Diversity, 2025)
Purpose:This research was conducted on Shopee marketplace consumers in RW 08, Pasirkaliki Village, North Cimahi District, Cimahi City. The purpose of this study was to determine the influence of online customer reviews and trust on purchasing decisions, both partially and simultaneously.Methodology:The research method used in this study is descriptive and associative. The unit of analysis is individuals, namely Shopee marketplace consumers in RW 08, Pasirkaliki Village, North Cimahi District, Cimahi City. The sample in this study was 100 respondents. The sampling technique used in this study was based on certain considerations or criteria. The analysis method used was multiple linear regression analysis, and the validity and reliability of the research instrument were also tested.Findings:Based on the research results it shows that there is a partial and simultaneous influence on the online customer review and trust variables on the purchasing decision variables.Implication:The influence of online customer reviews on purchasing decisions is 43.8%, while the influence of trust on purchasing decisions is 12.4%. The influence of online customer reviews and trust on purchasing decisions is 56.2%.